DIDACTIC IMPLICATIONS OF USING HISTORICALAPPROACH IN TEACHING THE CONCEPT OF GENE - Boujemaa, Agorram; Sabah, Selmaoui; Salah-Eddine, Khzami; Moncef, Zaki (European Scientific Journal, ESJ, 2015)
In this study, we present the results of the application of a historical approach in teaching the concept of gene. However, this is one of the most problematic concepts of genetics in both secondary and university levels. The approach consists of identifying and bringing out the conceptions of preservice teachers of biology. It aims in confronting the various historical models of the concept of "gene" built since its invention by Wilhelm Johansen in 1909 until the advent of molecular biology. These pre-service teachers act as scientists by carrying out a critical analysis of each of the six models listed in the literature. Also, they discussed its internal and external consistency as well as its limits. They suggest an alternative model which will be in turn analyzed and modified to reach the current model. Pre-service teachers are well aware of the cognitive processes and historical construction of this concept. They have the opportunity to review their spontaneous conceptions that hinder the construction of knowledge, in the consideration of historical scientific models. A test was administered to pre-service teachers before and after the activity. It consisted of a questionnaire about the concept of gene, its functions, and its related concepts. The same test was administered to a control group of pre-service teachers who received a classical instruction on the same subject. Therefore, this approach is more effective than the classical method because it allows an evolution of the conceptions of pre-service teachers.